Effects of canine adipose-derived mesenchymal stem cells on the epithelialization of rabbits' skin autograft (Oryctolagus cuniculus) - Alvarez Gómez, Jorge L. [UNESP]; Pazzini, Josiane M. [UNESP]; Barros, Michele A.; Morais, Bruna P.; Firmo, Bruna [UNESP]; Matsui, Andresa; Ampuero, Roberto [UNESP]; de Nardi, Andrigo B. [UNESP] (FapUNIFESP (SciELO), 2020)
The present study aimed to evaluate the effects of mesenchymal stem cells derived from canine adipose tissue in the healing process of full-thickness mesh skin grafts in rabbits. The stem cells were collected from young dogs; and, after characterization, remained in cryopreservation, in independent doses containing 2 x 106 cells. The mesh distal limb graft technique was performed in 60 rabbits, divided into three groups, CG (Control Group), GT1 (Intralesional Stem Cell Treated Group), and GT2 (Intravenous Stem Cell Treated Group), containing 20 animals each. After grafting, each group was randomly divided into four subgroups according to euthanasia time 3, 7, 14, and 30 days, containing five animals in each group. Animals of GT1_14, GT1_30, and GT2_14, GT2_30 subgroups received a second dose of xenogeneic cells on the seventh day. Meanwhile, animals from GT1_30 and GT2_30 received the third dose of xenogeneic cells on day 14. The groups treated with xenogeneic stem cells positively affected type III collagen re-epithelialization and deposition, and possibly GT1 had a controlled inflammatory response. However, no effect on angiogenesis. Thus, it was possible to demonstrate tolerance and therapeutic action of mesenchymal stem cells from canine adipose tissue in skin grafts in rabbits.
Keywords: Angiogenesis; Canine; Epithelialization; Healing; Mesh grafts; Oryctolagus cuniculus xenogens; Rabbits; Revascularization; Skin autograft; Stem cells